Compact multiband microstrip patch antenna with slot-rings for wireless applications - Nataraj, Chandrasekharan; Ismael, Assia Ali; Selvaperumal, Sathish Kumar; Khan, Sheroz (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper presents the design of compact microstrip patch antenna operating at multiple frequency bands. The antenna has traditional structure of microstrip patch combined with two ring slots and two semicircular slots at the edges. The antenna is designed with dimensions of 24.25 x 31.43 x 3.5 mm on a TD/Duroid 6002 substrate having a relative permittivity of 2.94. The antenna has a good bandwidth of 90 MHz (3.17-3.26 GHz) at 3.2 GHz WiMAX technology, 80 MHz (3.55.2.63 GHz) at 3.6 KHz for mobile broadband (MBB) frequency and 465 MHz at range from 4.85-to-5.16 GHz for Wireless Local Area Network (WLAN) (802.11a/h/j/n/ac). The antenna meets the 2:1 VSWR at the selected center frequencies. The designed antenna able to produce a maximum gain of 7.15dB at 4.82 GHz. The antenna has good bandwidth and reasonable efficiency for the wireless communication applications.